Teori Filosofis Revolusi Mental - Gunardi Endro (Center for Philosophy and Ethics, 2020)
Human mentality grows from the functioning of affective, cognitive and conative abilities in such an integrative, accumulative and directional way that its boundary is recognized by itself. It implies a trichotomy framework of human realms, consisting of physical realm, mental realm and metaphysical realm, on which human mentality development should be based. The problem is that the mentality that grows among the victims of colonialism and imperialism tends to be deformative, thus fostering a cultural system that in turn continues to breed a deformative mentality. The failure of the inward-oriented function (synthesis) makes the vicious circle of the growth process of deformative mentality difficult to break. The solution is a mental revolution through political intervention to restore the power of synthesis (inward). The realization is by reversing the growth pattern to be more in favor of the growth of the power of synthesis (inward) rather than the power of analysis (outward) so that in the end a balanced systemic and systematic growth of mentality is established.